Building microservices with Spring Boot LiveLessons - Long, Josh (LiveLessons, 2017)
"In this video training, Josh Long and Phil Webb demonstrate how and why Spring and Spring Boot offer the best way to build modern microservice systems. They look at the technologies and use-cases common to cloud-native microservice style applications as part of a larger framework, and then specifically address microservice implementation patterns."--Resource description page.